2014
DOI: 10.12988/ces.2014.3951
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-dimensional three-zone combustion model of the Diesel engine to calculate performances and emission using the Diesel-ethanol dual fuel

Abstract: In the present study, develop the multi zone thermodynamic model for the simulation of a small diesel engine operating on the mixture of diesel and ethanol and comparing results with an experiment. This paper discussed analytically and provides data of nitrogen oxide and performance parameters such as power, speci-20 Paramust Juntarakod and Thanakom Soontornchainacksaeng fic fuel consumption and thermal efficiency, indicated mean effective pressure. For this purpose, quasi-dimensional phenomenological three zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In their study, [10] concluded the use of additional zone lead to increased heat release prediction. Furthermore, [11] observed increased engine performance using a three-zone model for predicting the effect of ethanol with diesel fuel. Several researches have been carried out on the use of a modeling approach for optimization of combustion processes.…”
Section: Introductionmentioning
confidence: 94%
“…In their study, [10] concluded the use of additional zone lead to increased heat release prediction. Furthermore, [11] observed increased engine performance using a three-zone model for predicting the effect of ethanol with diesel fuel. Several researches have been carried out on the use of a modeling approach for optimization of combustion processes.…”
Section: Introductionmentioning
confidence: 94%
“…The paper investigates the influence of split fuel injection on the emission of solid particles and nitrogen oxides, using three different injection schemes. In Reference [21], the development and application of a zero-dimensional model with three zones for the analysis of the operating parameters of a high-speed diesel engine are presented. In Reference [22], a three-zone model is described that is applicable in real-time applications.…”
Section: No No X Emission Reduction Technology Expected Reductionmentioning
confidence: 99%
“…There was a very good agreement between the results from the simulation program and the experimental results carried out on a "Hydra" test bench. Paramust Juntarakod et al [9] have carried out numerical and experimental studies on the diesel/ethanol mixture injected into a combustion chamber of diesel engines by developing a multi-zone combustion model. The results show a remarkable increase in maximum performance parameters with increased engine speed and equivalence ratio.…”
Section: Introductionmentioning
confidence: 99%